Deletion in Syndrome Compounds Perspective Antarah Bin Shaddad: An applied grammatical study - Faiz Shuaib Adam (Mantiqu Tayr: Journal of Arabic Language, 2021)
The deletion in the syndromic compounds is a syntactic phenomenon that deals with the syntactic changes that occur to the Arabic sentence in deleting one of the compounds, and the compounds associated with this concept are those terms that the owner does not separate from the other, And its deletion is one of the characteristics of the Arabic language, the structure of the economy in the composition, and the structure of that deletion builds on several purposes and grammatical errors that suggest and summarize that. The research deals with these compounds contained in the commentary of Antarah bin Shaddad, who is one of the knights ’poets from the pre-Islamic era, because of the large number of these omissions in this comment.